The trophic evolution of Lake Iseo as related to its holomixis - Rosario MOSELLO; Michela ROGORA; Valeria MEZZANOTTE; Maria Cristina BRIZZIO; Letizia GARIBALDI (Journal of Limnology, 1999)
Lake Iseo is undergoing a progressive deterioration in water quality, mainly due to eutrophication. This paper, based on measurements performed on the main tributaries and the outflow, considers the phosphorus, nitrogen and silica budget of the lake, related to its trophic evolution. The chief conclusion of the study is that the significant reduction in P load over the last few years following the construction of treatment plants is not enough to reverse the trend to eutrophication and the progressive deterioration in water quality. An attempt to use the OECD statistical approach to quantify the relationships between P load and the trophic condition of the lake yielded poor results, because the characteristics of the lake did not fulfil the hypothesis of the model. The reduced tendency to a complete overturn of the water is one of the most important aspects, leading to hypolimnion anoxia and P release from the sediments.